Pengaruh Financial Socialization, Financial Knowledge Dan Financial Behavior Terhadap Financial Well-Being (Studi Kasus Pada Ibu Rumah Tangga Desa Wandanpuro, Kecamatan Bululawang, Kabupaten Malang) - Syahputra, Arya Septya; Mahardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to examine Financial Socialization, Financial Knowledge and Financial Behavior towards Financial Well-Being among Housewives in Wandanpuro village, Bululawang District, Malang Regency. The sample selection method used in this research is proportional random sampling, where all members of the population are determined in proportion to the size of the group and taken randomly, then a total of 96 respondents are found. This research method uses multiple linear regression analysis with the SPSS version 26 analysis tool. The results of this research show that Financial Socialization (X1) has a positive and significant effect on Financial Well-Being, Financial Knowledge (X2) has no significant effect on Financial Well-Being, Financial Behavior (X3) has a positive and significant effect on Financial Well-Being, and simultaneously Financial Socialization, Financial Knowledge, and Financial Behavior have a significant effect on Financial Well-Being. Keywords : Financial Socialization, Financial Knowledge, Financial Behavior Financial Well-Being.